Efficacy of Neuro-Optometric Rehabilitation Therapy on the Visual Consequences of Acquired Brain Injury. - McCormack, Niall (Optometry & Visual Performance, 2021)
Neuro-optometric rehabilitation is a recognised intervention for treating visual dysfunctions resulting from acquired brain injury and is practised by a small but enthusiastic group within the profession of optometry. The use of evidence-based medicine has become increasingly important to support the integrity and acceptance of treatment and management of patients within this population. Although this discipline has made great strides in recent times and is becoming increasingly included in multi-disciplinary management, the volume of literature initially has been relatively light and dominated by a small number of researchers. This paper considers some of the most recent research supporting the use of neuro-optometry in the management of patients with visual conditions related to acquired brain injury. As optometrists are seeing increasing numbers of patients with traumatic brain injury/concussion, significant emphasis has been placed on these areas.